Effect of Storage Period and Irradiation Doses on Red Chillies - Abrar, Muhammad; Anjum, Faqir Muhammad; Zahoor, Tahir; Nawaz, Haq (Pakistan Journal of Nutrition, 2009)
The samples of red chillies were packed in High Density Polyethylene (HDPE) bags and irradiated using 2, 4 and 6 kGy gamma radiation. The irradiated samples were stored at room temperature and relative humidity along with control (0 kGy) for 90 days. The samples were evaluated for proximate composition, total phenolics and aflatoxin. Irradiation and storage showed non-significant effect on proximate composition and total phenolics whereas irradiation showed significant effect on aflatoxins as compared to control. There was gradual decrease in aflatoxin contents with the increase level of gamma rays. It was concluded that red chillies for better quality retention can be safely stored in polyethylene bags. The use of radiation can be helpful for the preservation of chillies with respect to the production of aflatoxin during storage.